2019
DOI: 10.4103/jomfp.jomfp_194_18
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Mycobacterium tuberculosis and Mycobacterium avium complex in human immunodeficiency virus-infected individuals with and without tuberculosis

Abstract: Context: For a dental practitioner, HIV-TB co-infection which is a lethal aliment is an occupational hazard by the virtue of abundant aerosol formation in day to day dental practice. Aim: To assess the prevalence of TB co-infection among HIV patients. To assess the infectivity by culturing Mycobacterium Tuberculosis and Mycobacterium avium complex using Lowenstein Jensen medium and Middlebrook medium. Setting and Design: One hundred and forty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In dental clinics, aerosols generated through drills and scalers can potentially splatter or aerosolise and move within the indoor environment. Body fluids or blood from patients may harbour viruses (such as mumps, measles, rubella, HSV 1 and 2, HIV, HBV, SARS-CoV, influenza A H5N1, influenza A H1N1, MERS-CoV or SARs-CoV-2), or bacterial pathogens (such as Mycobacterium tuberculosis or Legionella pneumophilla) some of which can be transmitted through aerosols and water mists [16][17][18][19][20][21][22]. Studies in nursing home and long-term care-home residents have shown that infections account for 27% to 63% of hospitalizations in the United States [23].…”
Section: Introductionmentioning
confidence: 99%
“…In dental clinics, aerosols generated through drills and scalers can potentially splatter or aerosolise and move within the indoor environment. Body fluids or blood from patients may harbour viruses (such as mumps, measles, rubella, HSV 1 and 2, HIV, HBV, SARS-CoV, influenza A H5N1, influenza A H1N1, MERS-CoV or SARs-CoV-2), or bacterial pathogens (such as Mycobacterium tuberculosis or Legionella pneumophilla) some of which can be transmitted through aerosols and water mists [16][17][18][19][20][21][22]. Studies in nursing home and long-term care-home residents have shown that infections account for 27% to 63% of hospitalizations in the United States [23].…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of the demonstration of acid-fast bacilli in histological specimens is low, as there is a relative scarcity of tubercle bacilli in oral biopsies. [9]…”
Section: Introductionmentioning
confidence: 99%